Stabilization of kaolinitic clay soil using silica fume, eggshell ash and lime - Muhammad Syamsul Imran, Zaini; Muzamir, Hasan (The Geomate International Society, 2023)
Soft kaolin clay is a problematic soils encountered in various construction projects that lead to the implementation of soil stabilisation. The utilisation of industrial and agricultural wastes in altering the characteristics of kaolinitic soil can be considered as an ideal solution to enhance the characterisation of problematic soils in the field of construction. To assess the impact of silica fume, eggshell ash, and lime on the various characteristics of kaolinitic soil, a series of laboratory experiments containing Atterberg limits, specific gravity, compaction test, unconfined compression test, X-ray fluorescence, X-ray diffraction, sieve analysis, and field emission scanning electron microscope is carried out. In this study, 2%, 4% and 6% of silica fume, 3%, 6% and 9% of eggshell ash and lime and the optimal combination of silica fume, eggshell ash with 3%, 6% and 9% of lime are used. The results present that the optimal utilization of silica fume, eggshell ash, and lime can alter the engineering characteristics of the soft kaolin clay by reducing the specific gravity, consistency limits, linear shrinkage, and maximum dry density, while increasing the value of optimum moisture content. In terms of strength improvement, the highest unconfined compression strength was recorded when soft kaolin clay was treated with 6% silica fume, 6% eggshell ash and 9% of lime is 81.03%. Therefore, this study concludes that optimal use of silica fume, eggshell ash, and lime can alter the characteristics of kaolinitic soil and open the way to economical and sustainable materials in improving the problem soil.